2018
DOI: 10.1186/s12942-018-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Domestic gardens and self-reported health: a national population study

Abstract: BackgroundThere is a growing recognition of the health benefits of the natural environment. Whilst domestic gardens account for a significant proportion of greenspace in urban areas, few studies, and no population level studies, have investigated their potential health benefits. With gardens offering immediate interaction with nature on our doorsteps, we hypothesise that garden size will affect general health—with smaller domestic gardens associated with poorer health.MethodsA small area ecological design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Many of the observations about animals and bird song came from people's gardens or views from their home windows, highlighting the importance of having access to a garden and green views as a common and frequent 'point of contact' with nature (Cameron et al, 2012). This is consistent with correlational analysis which found that garden size was significantly associated with wellbeing, even when considering other variables such as socioeconomic status (Brindley, Jorgensen, & Maheswaran, 2018). The theme with the second largest representation of observations was that of expressing gratitude at having street trees along commutes to work and university; and enjoying seeing street trees out of office or home windows.…”
Section: Main Themessupporting
confidence: 62%
“…Many of the observations about animals and bird song came from people's gardens or views from their home windows, highlighting the importance of having access to a garden and green views as a common and frequent 'point of contact' with nature (Cameron et al, 2012). This is consistent with correlational analysis which found that garden size was significantly associated with wellbeing, even when considering other variables such as socioeconomic status (Brindley, Jorgensen, & Maheswaran, 2018). The theme with the second largest representation of observations was that of expressing gratitude at having street trees along commutes to work and university; and enjoying seeing street trees out of office or home windows.…”
Section: Main Themessupporting
confidence: 62%
“…Importantly, this type of interconnected lifestyle comes with a rich exposure to diverse microbiota and the associated health benefits common to traditional and agricultural communities [52]. Urban residents surrounded by more green space tend to be healthier, regardless of socioeconomic status [53]. As previously discussed, diverse microbiota are fundamental to good human health.…”
Section: Microbiome Rewilding and Planetary Healthmentioning
confidence: 97%
“…The natural world is increasingly viewed as being salutogenic, with good numbers of studies linking aspects of nature (Fuller et al 2007;McMahan and Estes 2015;Wood et al 2018) and green spaces (Wheeler et al 2015;Markevych et al 2017;Brindley et al 2018;Tost et al 2019) to human health and well-being. In a world that is rapidly urbanising, however, access to nature and green spaces can be restricted owing to densification or urban sprawl (Haaland and van den Bosch 2015), and provision of green space not being prioritised within city planning (Moseley et al 2013;Sanesi et al 2017;Douglas et al 2019).…”
Section: Introductionmentioning
confidence: 99%